Gilles Deleuze and the Missing Architecture. Issue 2 (May 2014) - Jobst, Marko
<x xml:space="preserve">Abstract</x> This essay combines experiential writing, quotes from Virginia Woolf's novel The Waves and Gilles Deleuze's philosophy in order to indicate that architecture remains a largely overlooked instance of the world. This is particularly problematic in the context of the question of immanence, which can be understood to lie at the core of Deleuze's philosophy. Architecture's relation to thought is discussed here via Deleuze's writing in Difference and Repetition and pursued in conjunction with Simone Brott's notion of architectural 'effects'. Rather than seeing encounters with architecture as the site of recognition of the habitual and routine, our experience of architecture-as-world should be understood to ceaselessly contribute to the emergence of thought. Brian Massumi's writing offers one potential direction to pursue, via the notion of the diagram tied to experience before it is fed into the loop of architectural design and its accompanying representational techniques.